Process dynamics, modeling, and control - Ogunnaike, Babatunde A. (Babatunde Ayodeji) (Topics in chemical engineering (Oxford University Press), 1994)
Synopsis: This text offers a modern view of process control in the context of today's technology. It provides the standard material in a coherent presentation and uses a notation that is more consistent with the research literature in process control. Topics that are unique include a unified approach to model representations, process model formation and process identification, multivariable control, statistical quality control, and model-based control. This book is designed to be used as an introductory text for undergraduate courses in process dynamics and control. In addition to chemical engineering courses, the text would also be suitable for such courses taught in mechanical, nuclear, industrial, and metallurgical engineering departments. The material is organized so that modern concepts are presented to the student but details of the most advanced material are left to later chapters. The text material has been developed, refined, and classroom tested over the last 10-15 years at the University of Wisconsin and more recently at the University of Delaware. As part of the course at Wisconsin, a laboratory has been developed to allow the students hands-on experience with measurement instruments, real time computers, and experimental process dynamics and control problems.